Romantismus, osvícenství a fantastický hrdina - Nikola Balaš (AntropoWebzin, 2010)
This article attempts to discover the roots of fantastic literature. In comparison with popular opinion of fantasy being a succesor of romanticism, this article shows that the popular opinion constitutes only half of the truth. Admittedly works of C. S. Lewis, J. R. R. Tolkien or R. E. Howard share distinctive romantic elements – enmity toward modernity, longing for traditional society or love for the nature. Nevertheless there is a tangible evidence that fantasy as a literary, movie or video game genre has much in common with enlightenment world-view. Prime example of this influence is the archetype of fantastic hero. Usually individualistic in essence fantastic heroes confront their nefarious adversaries in order emerge victoriously in the end. With emphasis on autonomy and individual authenticity behaviour of those literary heroes therefore serves as a pattern for modern people to follow. Is fantasy genre either to be understood as a sort of escapist literature or as an user manual for living in modern world?